Cross-sectional seasonalities in international government bond returns - Zaremba, Adam (Journal of Banking & Finance, 2019)
We are the first to document the cross-sectional return seasonality effect in international government bonds. Using a variety of tests, we examine fixed-income securities from 22 countries for the years 1980–2018. The bonds with high (low) returns in the same-calendar month in the past continue to overperform (underperform) in the future. The effect is robust to many considerations, including controlling for established predictors of bond returns. Our results support the behavioural story of the anomaly, demonstrating its highest profitability in the periods of elevated investor sentiment and in the market segments of strong limits to arbitrage. Nonetheless, investment application of bond seasonality might be challenging due to high trading costs and the required short holding periods.